2000
DOI: 10.1007/pl00000707
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock effects on cell cycle progression

Abstract: In mammalian cells, short-term (acute) exposure to a moderate heat shock leads to a transient arrest of cells at mainly two cell cycle checkpoints, the G1/S and G2/M transitions. This is documented by the more or less synchronous resumption of cell cycle progression from these checkpoints during recovery. The reason for the accumulation of cells at these checkpoints may be found in activity thresholds of cyclin-dependent kinases (Cdks) at both transitions which are determined by (i) the amounts of the responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 118 publications
8
91
1
2
Order By: Relevance
“…Studies have indicated that heat stress induces disturbance in the percentages of chicken thymocytes in G0/G1, S, and G2/M phases (Zhang et al 2003), resulting in a large number of lymphocytes arrested in S and G2/M phases. Animals alleviate the harm of heat stress by increased cell proliferation (Kuhl et al 2000). In this study, we found that the percentage of lymphocytes in the G2/M phase of HS group was consistent with the increase in the apoptosis rate of thymocytes in doi: 10.17221/67/2015-CJAS chicks after heat stress, and both of them reached the maximum at 6 weeks of age.…”
Section: Discussionsupporting
confidence: 81%
“…Studies have indicated that heat stress induces disturbance in the percentages of chicken thymocytes in G0/G1, S, and G2/M phases (Zhang et al 2003), resulting in a large number of lymphocytes arrested in S and G2/M phases. Animals alleviate the harm of heat stress by increased cell proliferation (Kuhl et al 2000). In this study, we found that the percentage of lymphocytes in the G2/M phase of HS group was consistent with the increase in the apoptosis rate of thymocytes in doi: 10.17221/67/2015-CJAS chicks after heat stress, and both of them reached the maximum at 6 weeks of age.…”
Section: Discussionsupporting
confidence: 81%
“…It may be that during our two week cultivation period, explants were protected by overexpression of heat shock proteins followed by induction of growth factor expression, similarly to the findings reported in mouse tumour development 39. Moreover, a positive effect on growth was suggested to arise from the inhibition of protein synthesis of negative growth regulators 40. However, at the end of culture, the ability for cell proliferation was lower than in controls, which can be explained by the fact that terminal differentiation that we find occurs after the exit from the cell cycle.…”
Section: Discussionsupporting
confidence: 79%
“…As the distribution of 1n, 2n, and 4n cells remained almost constant during HS ( Figure 2B), cells apparently were cell cycle arrested in both G1 (unreplicated DNA = 1n) and G2 phases (after DNA replication $ 2n, 4n), perhaps as a consequence of reduced activities of cyclin-dependent kinases (Kühl and Rensing, 2000). As presumably in all eukaryotes, including Chlamydomonas, the (A) Behavior of TAG clusters.…”
Section: Cells Undergo An Immediate Cell Cycle Arrest Upon Onset Of Hsmentioning
confidence: 82%